Telomere length as a biomarker for adiposity changes after a multidisciplinary intervention in overweight/obese adolescents: the EVASYON study. - Sonia García-Calzón (Public Library of Science (PLoS), 2014)
Context Telomeres are biomarkers of biological aging. Shorter telomeres have been associated with increased adiposity in adults. However, this relationship remains unclear in children and adolescents. Objective To evaluate the association between telomere length (TL) and adiposity markers in overweight/obese adolescents after an intensive program. We hypothesize that greater TL at baseline would predict a better response to a weight loss treatment. Design setting patients and intervention The EVASYON is a multidisciplinary treatment program for adolescents with overweight and obesity that is aimed at applying the intervention to all possibly involved areas of the individual, such as dietary habits, physical activity and cognitive and psychological profiles. Seventy-four participants (36 males, 38 females, 12-16 yr) were enrolled in the intervention program: 2 months of an energy-restricted diet and a follow-up period (6 months). Main outcome TL was measured by quantitative real-time polymerase chain reaction at baseline and after 2 months; meanwhile, anthropometric variables were also assessed after 6 months of follow-up. Results TL lengthened in participants during the intensive period (+1.9±1.0, p<0.001) being greater in overweight/obese adolescents with the shortest telomeres at baseline (r = -0.962, p<0.001). Multivariable linear regression analysis showed that higher baseline TL significantly predicted a higher decrease in body weight (B = -1.53, p = 0.005; B = -2.25, p = 0.047) and in standard deviation score for body mass index (BMI-SDS) (B = -0.22, p = 0.010; B = -0.47, p = 0.005) after the intensive and extensive period treatment respectively, in boys. Conclusion Our study shows that a weight loss intervention is accompanied by a significant increase in TL in overweight/obese adolescents. Moreover, we suggest that initial longer TL could be a potential predictor for a better weight loss response.